Scientific-practical results of monitoring anthropogenic influence upon environment of mining territories - Kachurin Nikolay; Komaschenko Vitaliy; Golik Vladimir; Morkun Volodymyr (E3S Web of Conferences, 2018)
The objective of this paper is to improve the ecological monitoring system and to take effective technological measures by way of wastes neutralization. The scientific-practical results of monitoring the anthropogenic influence upon the environment of mining-industrial territories were discussed. The global environmental problems of modernity are connected only with the anthropogenic pollution of the atmosphere. Pollution by hazardous substances at various enterprises harms health and disrupts the dynamic balance of natural systems. It is especially typical for mining-industrial region territories. The solution of the problem of environmentally optimal distributing resources for industrial enterprises of the mining-industrial region will allow making maximal profit from each enterprise by assumption of reducing anthropogenic influence upon environment up to the maximum permissible value, which is specified by normative documents. The patterns of formation of mining enterprises influence consequences on the atmosphere have been improved with the use of experimental and theoretical studies and in order to optimize the resources distribution for preventive measures, which can ensure the atmospheric safety of the mining-industrial region. The proposed methodological principles for a comprehensive assessment of the atmosphere of the mining-industrial region allow to implement an integrated approach to forecasting the intensity of atmospheric pollution, the economic efficiency of production and atmospheric air condition control, using the basic requirements of the environmental imperative for the territory under consideration.